2019
DOI: 10.18203/2349-3291.ijcp20190428
|View full text |Cite
|
Sign up to set email alerts
|

A study to evaluate the prognostic significance of thrombocytopenia among critically ill children

Abstract: Background: Pediatric critical care differs from Adult critical care not only in age but also in the outcomes. There are no studies regarding thrombocytopenia in the pediatric population. Therefore, in the current study, our objective was to study the prevalence and, the severity of thrombocytopenia, clinical features, and prognostic significance of low platelet count as an independent predictor of mortality and prolonged hospital and ICU stay.Methods: This was a prospective observational study conducted at te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…Similar results were observed in the study conducted by Sah et al [15] where maximum (41.7%) patients had mild thrombocytopaenia (platelet count <150 × 10 9 /L) followed by 32.3% of patients with moderate thrombocytopaenia (platelet count <100 × 10 9 /L) and 26.4% of patients with severe thrombocytopaenia (platelet count <50 × 10 9 /L). Studies conducted by Mundkur et al [18] and Kaur et al [1] who showed higher prevalence of severe thrombocytopaenia 51% (platelet count <50 × 10 9 /L) whereas the study by Yilmaz et al [6] showed lower prevalence (7.45%) of severe thrombocytopaenia as compared to our study. Thus, there is varying prevalence of severity of thrombocytopaenia.…”
Section: Severity Of Thrombocytopaeniacontrasting
confidence: 82%
See 3 more Smart Citations
“…Similar results were observed in the study conducted by Sah et al [15] where maximum (41.7%) patients had mild thrombocytopaenia (platelet count <150 × 10 9 /L) followed by 32.3% of patients with moderate thrombocytopaenia (platelet count <100 × 10 9 /L) and 26.4% of patients with severe thrombocytopaenia (platelet count <50 × 10 9 /L). Studies conducted by Mundkur et al [18] and Kaur et al [1] who showed higher prevalence of severe thrombocytopaenia 51% (platelet count <50 × 10 9 /L) whereas the study by Yilmaz et al [6] showed lower prevalence (7.45%) of severe thrombocytopaenia as compared to our study. Thus, there is varying prevalence of severity of thrombocytopaenia.…”
Section: Severity Of Thrombocytopaeniacontrasting
confidence: 82%
“…Maximum age range was 1 month-18 years in the study of Mundkur et al [18] The mean age of the patients in the present study was 5.4 years which is similar to the studies conducted by Mittal et al [19] and Mussa et al [16] The range of age groups of the study population in this study was 1 month-17 years, which is similar to that of the study by Mundkur et al [18] who had included patients from 1 month to 18 years of age. The median age observed in our study was 36 months (3 years), which is similar to the study by Agrawal et al [7] (2008), where a median age was 32 months.…”
Section: Agementioning
confidence: 91%
See 2 more Smart Citations